METHODOLOGICAL BASIS FOR EVALUATING THE QUALITY OF BUSINESS PROCESS MANAGEMENT WITH THE GOAL OF ACHIEVING SUSTAINABLE DEVELOPMENT OBJECTIVES - Glukh, Vadym (Sworld-Us Conference proceedings, 2025)
This study examines methodological approaches to assessing the quality of business process management in construction companies in the context of sustainable development. The purpose of the study is to develop a methodology for the overall assessment of t